Penerapan Smart Trash Monitoring System untuk Memantau Sampah Rumah Tangga di Perumahan Graha Panyindangan Estate Indramayu - Fauzan Ishlakhuddin; Esti Mulyani; Eka Ismantohadi (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
Household waste management remains a critical challenge in creating clean and sustainable residential environments. Manual monitoring methods often lead to delayed waste collection, overflowing bins, and operational inefficiency. This community engagement program implements an Internet of Things (IoT)-based Smart Trash Monitoring SIstem (STMS) at Graha Panyindangan Estate, Indramayu. The sIstem utilizes ultrasonic sensors and ESP32 microcontrollers to detect the fill level of household waste containers and transmit data in real time to a user-accessible dashboard. The results demonstrate that the STMS provides accurate waste-level information, reduces manual inspections, enhances collection efficiency, and fosters data-driven behavior among residents. Social changes also emerged, including improved environmental awareness, new social norms, and the emergence of local leaders supporting sIstem sustainability. This program contributes to the realization of smart living in modern residential communities, ensuring better waste management, cleaner environments, and more sustainable practices for future generations. It also provides valuable insights into the role of technology in addressing environmental issues at the community level.